The Implication of UNHCR in Addressing the Problem of Afghan Refugees Against Global Security Stability - Syifa Kurnia; Rena Febriana (TRANSBORDERS: International Relations Journal, 2022)
This article aims to examine the implications of the United Nations High Commissioner for Refugees (UNHCR) in dealing with the problem of Afghan refugees scattered in various countries caused by the internal conflict between the Afghan government and the Taliban. The role of UNHCR under the 1951 Refugee Convention and the 1967 Protocol contains the objectives of protecting the rights of refugees throughout the world and providing various facilities both in the health sector and to regulate the placement of refugees in third countries. The international community is feeling the impact of the COVID-19 pandemic. In its implementation, the distribution of Afghan refugees to the destination countries often raises a new problem for the country concerned with security stability. There is a new problem that the Afghan government is also facing due to several countries being less willing to accept the large number of refugees arriving. In understanding the condition of the problem, a qualitative analysis approach is used by observing the strategies taken by UNHCR. This article finds that UNHCR, which acts as a facilitator, mediator, and initiator, has a significant role in preventing global threats due to the high flow of refugees. In this way, it can realize the rights of refugees and the international security stability to be achieved.